Development of Constructivism-Based Learning Models to Improve Student Learning Outcomes - Hiba Dertyana Siregar; Astuti Salim; Mirna Riazil Jannah; Ayu Nurkhayati; Nurul Hidayati (CV. Get Press Indonesia, 2025)
This study develops and evaluates a constructivism-based learning model aimed at enhancing student learning outcomes. Grounded in the philosophy that knowledge is actively constructed by learners, this model engages students through meaningful activities fostering critical thinking, creativity, and collaboration. Employing a research and development (R&D) approach with ADDIE phases (Analyze, Design, Develop, Implement, Evaluate), the model was tested across multiple schools with quantitative pretest-posttest and qualitative observations. Results demonstrated significant improvements in cognitive achievement, motivation, and active participation, with students showing deeper understanding and problem-solving skills. The study confirms constructivist strategies’ effectiveness in diverse educational contexts and highlights the crucial role of teachers as facilitators. Recommendations include integrating digital tools and extending implementation to higher education levels. Overall, this research underscores the potential of constructivism-based learning models to transform education by fostering active, learner-centered environments that improve academic success and lifelong learning skills.